Optimasi Dual Axis Tracking Untuk Solar Cell Berbasis Imperialis Competitive Algorithm (ICA) - Mohammad Hasib Al Isbilly; Tubagus Fahm; Markhaban Siswanto (FT- UNDAR, 2019)
The use of fossil energy as an electric fuel causes the earth to experience global-warming. As a tropical country, Indonesia has great potential to develop solar energy as a substitute for fossil energy. Increased efficiency in capturing sunlight will further optimize the work of the Solar Power Plant (PLTS). One way that can be done is by making a solar tracker so that the Solar Panel can follow the direction of the sun's motion. Optimization Design The solar tracker uses dual axis using Proportional Integral Differential (PID) control tuned with the Imperialis Competitive Algorithm (ICA), which is expected to be able to get the right angle between the yaw and Pitch with Azimuth and Elevation Angle. The PID-ICA controller design is done using matlab software. For vertical and horizontal rotary axes it is expected to obtain the best PID-ICA constant, which in turn will affect the performance and optimization of the photovoltaic system. The best optimization results using ICA-based PID with a settling time value of 0.0906 s on the horizontal axis and 0.094 s on the vertical axis